Trade openness, gains from variety and government spending - Sandra Hanslin (University of Zurich, Socioeconomic Institute, 2010)
This paper investigates empirically the effect of import diversity on government size and provides evidence for the love of variety effect on government spending described in Hanslin (2008). I argue that crowding out of firms is an important cost of public good provision. However, due to the access to foreign varieties, national costs of public good provision are lower and therefore, public good provision is higher. Especially for OECD countries this channel seems to exist. The diversity of imported products has a positive effect on government consumption, particularly when these goods are classified as differentiated. In addition, this positive effect is decreasing in home market size. Further, the direct effect of the share of differentiated in total imported products on the government share is negative.
Keywords: F10; H10; 330; international trade; trade openness; public expenditure; gains from variety; Handelsliberalisierung; Öffentliche Ausgaben; Internationale Arbeitsteilung; Allgemeines Gleichgewicht; Monopolistischer Wettbewerb; Theorie